Dukungan Keluarga Dan Tingkat Kecemasan Siswa SMA Dalam Menghadapi Ujian Akhir Semester - Feliciyanvi Uverni; Lusia Garsiana Yunita; Novita Elisabeth Daeli (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
Final semester exam is a learning evaluation that carried out after semester ends. Final semester exams are conducted to measure and assess student competency. In carrying out the exam, there are many things that need to be prepared, one of which is self-preparation. Students are prone to experience the risk of anxiety at certain moments, for example when they are about to carry out an exam. Factors that influence anxiety include environment, family, gender and age. The purpose of this study was to determine the relationship between family support and anxiety levels in high school students in facing their final semester exams. The research method used quantitative research using an analytic survey design with a cross sectional approach. Sampling technique uses purposive sampling. The population in this study are 300 student with sample study of 72 students. The results showed that there were 37 (51.4%) female gender, 47 (65.3%) 16 year old respondents, the majority of respondents received moderate family support as many as 42 respondents (58.3%) and the majority of respondents had anxiety levels being as much as 25 (34.7%). There is no significant relationship between family support and the level of anxiety in high school students who will take the final semester examination with a p-value of 0.995 (>0.05).